2019
DOI: 10.1371/journal.pcbi.1006666
|View full text |Cite
|
Sign up to set email alerts
|

Short-term synaptic depression can increase the rate of information transfer at a release site

Abstract: The release of neurotransmitters from synapses obeys complex and stochastic dynamics. Depending on the recent history of synaptic activation, many synapses depress the probability of releasing more neurotransmitter, which is known as synaptic depression. Our understanding of how synaptic depression affects the information efficacy, however, is limited. Here we propose a mathematically tractable model of both synchronous spike-evoked release and asynchronous release that permits us to quantify the information c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 72 publications
1
15
0
Order By: Relevance
“…Here, we use a computational model to investigate the relevance of energetic constraints to design and function of hippocampal synapses that are characterized by low initial release probabilities but marked activity-dependent STP. Previous studies of information transmission at cortical synapses considered short-time dynamics arising from vesicle depletion alone [20][21][22][23] , or made simplifying model assumptions about presynaptic organization (e.g., availability of at most one vesicle per release site) 9,24 , limiting their physiological relevance for describing facilitating hippocampal synapses.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we use a computational model to investigate the relevance of energetic constraints to design and function of hippocampal synapses that are characterized by low initial release probabilities but marked activity-dependent STP. Previous studies of information transmission at cortical synapses considered short-time dynamics arising from vesicle depletion alone [20][21][22][23] , or made simplifying model assumptions about presynaptic organization (e.g., availability of at most one vesicle per release site) 9,24 , limiting their physiological relevance for describing facilitating hippocampal synapses.…”
Section: Introductionmentioning
confidence: 99%
“…In doing so, this RRAM device has the capacity to mimic ionic mechanisms in synapses faithfully that enables efficient learning and data processing. [18][19][20][21][22][23][24] We also present an empirically-driven conduction-based model of our device.…”
mentioning
confidence: 99%
“…In previous work, we studied the information transmission in a synapse during short-term depression [ 9 , 12 ]. There, the state of the binary asymmetric channel, which models the synapse, depended on the history of the output .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have addressed the modulatory role of short-term depression on synaptic information transmission [ 7 , 8 , 9 ]. In contrast, the information rate of a facilitating synapse is not yet fully understood, though it has been suggested that short-term facilitation temporally filters the incoming spike train [ 10 ].…”
Section: Introductionmentioning
confidence: 99%